Photoelectrochemical Detection of L‐Cysteine with a Covalently Grafted ZnTAPc‐Gr‐based Probe. Issue 6 (11th February 2020) - Peng, Jinyun; Huang, Qing; Liu, Yuxia; Huang, Yingying; Zhang, Cuizhong; Xiang, Gang
Abstract: L‐cysteine plays a vital role in organisms, and is an important biomarker for many pathological diseases that seriously affect human health. In the study, a photoelectrochemical (PEC) probe with zinc‐tetramine phthalocyanine covalently grafted to graphene oxide (ZnTAPc‐Gr) was developed for L‐cysteine detection. Graphene oxide (GO) with carboxyl was used to immobilize zinc‐tetramine phthalocyanine (ZnTAPc) with amidogen (a graft structure formed by an amide covalent bond), which could firmly immobilize ZnTAPc, thereby improving the photoelectrochemical performance and stability. L‐cysteine molecule, an electron acceptor, was specifically recognized by the PEC probe, exhibiting a decrease in the photocurrent signal. Under the optimal experimental conditions, the fabricated PEC probe exhibited excellent performance in L‐cysteine analysis within a linear range of 0.25–113 μM and a detection limit of 11.4 nM. The PEC probe showed high sensitivity, selectivity, and stability. The method described herein provides an effective strategy for PEC probe construction for L‐cysteine detection, and can also serve as a promising PEC platform for the analyses of other small molecules. Abstract :